Perbaikan Tata Letak Lantai Produksi untuk Meminimasi Waktu Produksi dengan Menggunakan Metode Simulasi Pada PT. Argha Karya Prima Industry, Tbk - Indira Larasati; Parwadi Moengin; Sucipto Adisuwiryo (JURNAL TEKNIK INDUSTRI, 2018)
PT. Argha Prima Karya Industry is a company engaged in the field of flexible packaging. Problems found on the production floor of PT. Argha Karya Prima Industry is a delay in production time due to the engine distance that is too far and the availability of material handling is lacking. The product studied in this study is polyester plastic film with a production capacity of 1 unit within 11 hours equivalent to 2 days, while the production target set is 1 unit within 8 hours equivalent to 1 day. Layout the initial model of PT. Argha Karya Prima Industry was analyzed by simulation using ProModel software. Then after the initial layout was declared valid, improvements were made to the problems of the production floor layout using the Systematic Layout Planning method. From this method, two alternative layouts are obtained. The difference from the two proposed layouts is in the initial model, the slitter unwinder machine adjacent to the waste trimming area, while in the proposed layout 1, the slitter unwinder machine is located adjacent to the temporary storage rack. Then in the proposed layout 2, the slitter rewinder machine is adjacent to the finishing good area, while in the initial layout, the rewinder machine is adjacent to the temporary storage rack.